A numerical approach for response of whipple shields with coated and monolithic front bumper to hypervelocity impact by spherical projectiles. (January 2023) - Pai, Anand; Sharma, Arastu; Eby, Irene Mary; Kini, Chandrakant R.; Shenoy, Satish B.
Abstract: Orbital debris in space offers a constant threat to spacecraft, satellites, and the International Space Station (ISS). There is a growing concern as the number of satellites and other space objects keep increasing year-on-year with advancements in space exploration and orbital activities. The threat posed by the small debris or MMODs (micrometeoroid orbital debris) to satellites and spacecraft can be prevented using Whipple shields made of impact-resistant materials. In the current work, a numerical approach has been utilized to simulate hypervelocity impact of spherical projectiles of diameter 4 mm on monolithic and coated whipple shields to determine the extent of damage, and the deformation behaviour. The simulations were conducted at 3.5 km/s and 5.5 km/s. The computational work was carried out using AUTODYN® module of ANSYS® finite element software. Highlights: Numerical model replicates a popular hypervelocity impact experiment. Coated and monolithic front bumper response to impact studied. Velocity reduction, kinetic energy, internal energy, and penetration characteristics analysed. Debris cloud formation compared with similar experiments.